Susceptibility of Clinical Isolates of Candida to Photodynamic Effects of Curcumin - Dovigo, Livia N. [UNESP]; Pavarina, Ana C. [UNESP]; Carmello, Juliana C. [UNESP]; Machado, Ana L. [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Bagnato, Vanderlei S. (Wiley-Blackwell, 2011)
Background and Objective: The resistance of Candida species to antifungals represents a major challenge for therapeutic and prophylactic strategies. This study evaluated photodynamic therapy (PDT) mediated by Curcumin (CUR) against clinical isolates of C. albicans, C. tropicalis, and C. glabrata, both in planktonic and biofilm forms. Study Design/Materials and Methods: Suspensions of Candida were treated with three CUR concentrations and exposed to four LED fluences. The protocol that showed the best outcomes for inactivation of the planktonic phase was selected to be evaluated against Candida biofilms. In addition, two higher CUR concentrations were tested. The metabolic activity of biofilms was evaluated by means of XTT reduction assay and the biofilm biomass was evaluated using crystal violet (CV) staining assay. Data were analyzed in a mixed model nested ANOVA, Wilcoxon's nonparametric tests, and the Kruskal-Wallis test (alpha = 5%). Results: The use of CUR in association with light was able to promote a significant antifungal effect against the planktonic form of the yeasts. When using 40 mu M of CUR, the metabolic activity of C. albicans, C. glabrata, and C. tropicalis biofilms was reduced by 85%, 85%, and 73%, respectively, at 18 J/cm(2). CUR-mediated PDT also decreased the biofilm biomass of all species evaluated. In addition, CV staining showed that C. albicans isolates were strong biofilm-forming strains, when compared with C. glabrata and C. tropicalis isolates. Conclusion: The results from the present investigation showed that low CUR concentrations can be highly effective for inactivating Candida isolates when associated with light excitation. Lasers Surg. Med. 43: 927-934, 2011. (C) 2011 Wiley Periodicals, Inc.
Keywords: Candida albicans; Candida glabrata; Candida tropicalis; photodynamic therapy; turmeric